Design of wide ultrasonic horns based on topology optimization. Issue 6 (3rd June 2022) - Afshari, Mehran; Arezoo, Behrooz
ABSTRACT: In this article, a two-objective procedure is proposed to optimize the topology of wide horns. These two objectives are: the longitudinal natural frequency of the horn should be similar to the frequency of the driven transducer–booster, and the output face of the horn should vibrate uniformly. The weighted sum method is used to calculate the two-objective sensitivity number. Based on the proposed algorithm, three horns (bar, cylindrical and U-shaped bar) are designed. For these horns, optimum designs are obtained, the amplitude uniformities of which are improved by 67%, 19.5% and 584.5%, respectively, compared with the initial models. Also, the resonance frequencies of the bar and U-shaped bar horns are 0.25%, and 0.75% less than the target frequency and the resonance frequency of the cylindrical horn is 0.2% higher than the target frequency. To verify the results of the proposed algorithm, a well-designed bar horn is fabricated and tested. In the experimental results, the resonance frequency and uniformity of the horn are, respectively, 0.4% higher and 0.97% lower than the simulation results.